Social and Environmental Justice in Foreign Aid: a Case Study of Irrigation Interventions in Western Nepal - Clement, Floriane; Basnet, Govinda; Sugden, Fraser; Bharati, Luna (New Angle: Nepal Journal of Social Science and Public Policy, 2014)
Debates over the effectiveness of foreign aid have been recently revived both in the development sector and in the academia. International funding agencies have notably adopted new principles to improve aid delivery. Using the particular case study of a set of irrigation interventions in Western Nepal, we argue that these steps will not radically improve the pro-poor outcomes of aid interventions as long as the latter are framed in an apolitical, technical and managerial vision and discourse of development. We propose to adopt social and environmental justice as an analytical framework and vocabulary for action.